Cultivation modes impacting root microbiomes and metabolites in medicinal orchid Dendrobium denneanum - Chen, Lin; Ding, Haiyan; Chen, Xin; Wang, Jiaojiao; Hu, Yuan; Chen, Hongping; Liu, Youping (Frontiers in Microbiomes, 2023)
Introduction The plant microbiome is the second genome of plants and is important for plant growth and health. Dendrobium is an epiphytic herbal plant of the family Orchidaceae that is often found attached to tree trunks or rocks and exhibits different cultivation modes. Microbiological and metabolite studies of Dendrobium denneanum Kerr (D. denneanum) in different cultivation modes can reveal important relationships between Dendrobium spp., their microbiomes, and their pharmacological substances, which is important for sustainable agricultural development and human health, particularly in the study of medicinal plants. Methods In this study, three cultivation modes, living tree epiphytic (LT), stone epiphytic (SE), and pot cultivation (PO) of D. denneanum in the same environment were selected, and the metabolites were using ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS). Subsequently, differential metabolites were screened, the rhizosphere and root endosphere microorganisms were sequenced via high-throughput sequencing, and the 16S rRNA gene/ITS sequences were obtained. Results The main microbial taxa in the rhizosphere and root endosphere of D. denneanum included bacteria belonging to Proteobacteria, Actinobacteria, and Actinobacteria, and the fungi Basidiomycota and Ascomycota, whose abundances varied in different cultivation modes. Soil properties affect the composition of D. denneanum metabolites and root microbiome, among which, soil total phosphorus (TP) and pH in particular are important factors for soil microorganisms. Studies of root microbial communities have shown that root endosphere fungi are similar to rhizosphere fungi with microbial enrichment occurring from the external environment to the internal structures. Root microbial communities and metabolites correlation analyses revealed significant correlations between rhizosphere microbes, as well as endophytes and metabolites. For example, the rhizosphere bacterium genus Occallatibacter and root endosphere fungus Clonostachys showed a significant negative correlation with the pharmacodynamic substance gigantol in D. denneanum (P<0.05). Conclusion This study elucidates the effects of different cultivation modes on D. denneanum from the perspective of microorganisms and metabolites, and investigates the effects of root microorganisms on metabolites. The findings enhance the current understanding of root microorganisms in orchid plants and provide a theoretical basis for the cultivation of Dendrobium spp., represented here by D. denneanum.